2009
DOI: 10.1002/btpr.173
|View full text |Cite
|
Sign up to set email alerts
|

Insulin adsorption into porous charged membranes: Effect of the electrostatic interaction

Abstract: Insulin adsorption into a series of porous charged membranes was investigated by batch adsorption experiments, and the experimental results were analyzed by the homogeneous diffusion model. The membranes used in this study were prepared by pore-surface modification of porous poly(acrylonitrile) (PAN) membranes by grafting with weak acidic and basic functional groups. The amount of insulin adsorbed into the membrane was determined from the material balance of insulin. The insulin partition coefficient K between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Additionally, there is another possibility that the electrostatic attraction between the insulin and membrane changed the diffusion pattern of the insulin within the pores. 30,31 The determined values of k and D from the calculation of the diffusion characteristics are comparable to those obtained from the calculation of the adsorption kinetics, 6 as shown in the parenthesis of Table 2. The k and D values obtained in the present study seem to be reasonable when compared to the reported data of other proteins, such as BSA and lysozyme, 1,29,[32][33][34] which are of the order 10 À7 -10 À10 m/s and 10 À11 -10 À14 m 2 /s, respectively.…”
Section: Calculation Of the Diffusion Characteristicsmentioning
confidence: 92%
See 4 more Smart Citations
“…Additionally, there is another possibility that the electrostatic attraction between the insulin and membrane changed the diffusion pattern of the insulin within the pores. 30,31 The determined values of k and D from the calculation of the diffusion characteristics are comparable to those obtained from the calculation of the adsorption kinetics, 6 as shown in the parenthesis of Table 2. The k and D values obtained in the present study seem to be reasonable when compared to the reported data of other proteins, such as BSA and lysozyme, 1,29,[32][33][34] which are of the order 10 À7 -10 À10 m/s and 10 À11 -10 À14 m 2 /s, respectively.…”
Section: Calculation Of the Diffusion Characteristicsmentioning
confidence: 92%
“…6 As is described that k reveals the effect of the boundary layer between the membrane and solution. The decrease in k may be ascribed to the change in the boundary layer (increased thickness 27 or changed structure 28 ), because the insulin concentration near the membrane surface is expected to be much higher than that in the bulk when the insulin and membrane carries opposite charge.…”
Section: Calculation Of the Diffusion Characteristicsmentioning
confidence: 98%
See 3 more Smart Citations